Device Closure of Perimembranous Ventricular Septal Defect: Choosing Between Amplatzer Occluders - Haddad, Raymond N.; Daou, Linda; Saliba, Zakhia (Frontiers in Pediatrics, 2019)
Background: Off-label device closure of perimembranous ventricular septal defect (pmVSD) is well reported in the literature with encouraging results. However, technical challenges may be encountered. Objectives: To evaluate and compare feasibility, technical aspects, procedural outcomes and mid-term follow-up of pmVSD closure using AmplatzerTM occluders. Patients and Methods: From July 2015 to July 2018, patients in whom pmVSD closure was attempted using an Amplatzer occluder were retrospectively identified from our institution’s database. Device selection was made according to the defect anatomy that was obtained via ventriculography and trans-oesophageal echocardiography. Follow-up evaluations were done at discharge, then at 1, 3, 6, and 12 months and yearly thereafter with transthoracic echocardiography and electrocardiogram. Results: In total, 8 Amplatzer Duct Occluder (ADO), 27 ADO II and 17 Amplatzer Muscular VSD occluder (AMO) were used in 51 patients with a mean age of 7.4 ± 6.9 years and a mean weight of 25.4 ± 19.8 kg. Implantation was successful in 50/51 patients (98.0%). There was no procedure related mortality. One ADO accidentally embolized to the aorta, after release and was surgically recaptured from the iliac artery. All ADO II were delivered retrogradely with the least amount of time (p =0.002) and the lowest radiation exposure (p<0.001). Minor valvular disturbances occurred in 8/49 patients (16.3%), including five tricuspid regurgitation (three with ADOII and two with AMO) and three trivial aortic regurgitations (two with ADO and one with ADOII). On a median follow-up of 194 days (range, 60 - 895 days), no surgical device removal was necessary. At 6 months of follow-up, trivial residual shunt was present in 5/49 patients (10.2%), among which none occurred with ADO. One complete atrioventricular block was detected 18 months after ADO implantation and required permanent pacing. Conclusions: Transcatheter closure of PmVSD using Amplatzer occluders is feasible, safe and efficacious in properly selected patients. The major key factor behind high procedural success rate is proper device selection. ADOII is remarkably superior in terms of device softness, flexibility and faster implantation process. Yet, its use is limited to small defects with particular anatomy.